Interlaminar failure behavior of GLARE laminates under short-beam three-point-bending load. (15th July 2016) - Liu, Cheng; Du, Dandan; Li, Huaguan; Hu, Yubing; Xu, Yiwei; Tian, Jingming; Tao, Gang; Tao, Jie
Abstract: In this paper, interlaminar failure behavior of GLARE-3/2-0.3 laminates under short-beam three-point-bending load were investigated with various span length-to-specimen thickness ratios (L/h). Failure modes and damage characteristics at different loading stages were observed by Scanning Electron Microscopy (SEM) to assess the failure behavior. It was found that failure modes changed accordingly with varying L/h ratios. A valid shear dominant failure mode was obtained at the L/h ratio of 8. Moreover, there were significant differences in failure modes and damage characteristics among three GLARE variants. The results also showed that lay-up configuration of glass/epoxy layer strongly affected load-deflection response, especially the failure load, and corresponding failure mode.